Evaluation of The Physical Condition of Pencak Silat Athletes From The Macan Takeran Sacrament Competition Category - Mohamad Maliki Mustaqim; Fatkur Rohman Kafraw; Hijrin Fithroni; Heri Wahyudi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Martial arts is art defense self originating from Indonesia that is developing rapidly as well as demand mastery skills physical, technical, and tactical. For reach performance peak, athlete need undergo evaluation condition physique regularly. Although available various method test, observation at Sasana Macan Takeran show that evaluation physique Not yet Once done. In fact, at the event 6th Regent's Cup, many athlete experience fatigue in the third round. Therefore that, test physique required For identify deficiencies and measures readiness athletes, because condition optimal physical condition is very important success, especially in category match. Research This aim evaluate condition physique athlete martial arts martial arts category match at Sasana Macan Takeran. Research use approach descriptive quantitative with method surveys and instruments main in the form of tests and measurements. Subjects study consists of of the 17 athletes who regularly train and compete in the category match. Instrument covering nine test items, namely 20 m sprint, wall ball pass, push-up, sit up, Shut, Sit And Reach, IMT, vertical jump, and MFT. Data analyzed in a way quantitative using SPSS version 25. The results show that 3 athletes (18%) are categorized good, 11 (65%) moderate, 1 (6%) poor, and 2 (12%) very poor, with an average score of total 30.94 or in “medium” category.